Perbandingan Hukum dalam Pelaksanaan Lelang Online terhadap Properti di Indonesia dengan Vietnam - Ananda Wisnu (Jurnal Hukum Lex Generalis, 2025)
Auctions have been present in Indonesia since the Dutch era. Over time, auctions have developed, which were initially auctions carried out conventionally with the direct presence of participants, now property auctions can be carried out online. In the implementation of online auctions with property objects, it is usually supervised by the Directorate General of State Assets and strictly regulated to ensure transparency and legal certainty. Meanwhile, in Vietnam, online property auctions are growing rapidly, but they are managed by private auction companies with various regulations. This journal discusses the comparison of online property auctions. The results show that Indonesia has a series of procedures that are fully structured and supervised by the DKJN while Vietnam is more adaptive and decentralized.